The sociological study of social consequence of remote living family with emphasis on moving social capital (case of study are the construction resident workers in Tehran) - MORADLU, ROZITA MOHAMMADI; SAROKHANI, BAGHER; MOHAMMADI, ASGHAR (The journal of contemporary issues in business and government, 2021)
Family is a social institution ehich includes the basic elements of a society like a mirror and reflects social disorders . on the other hand family and specilly woman in the place of mother is one of the most importan factors which affects society . society cant be healthy without having healthy families . Family as a most important social institution has been drawn the attention of many thinkors an sociologists.many of the social capital theorists and analysts have mentioned family as being and important source of production or erosion of social capital because of its importance . on the other hand social capital concept dueto its nature and concept is related nearly to the all of the themes and issues in the field of humanity and sociology and recently has been raised as an effective social factor an health , function of family institution along with its effects on its members has a determining role . scientists have mentioned important points related to social functions of family institution they considay the role and function of family in social constructs as being complementary to the function of other social institutions and evaluate highly its effects on strengthening family safty . When ever mother or father leaves family ,the other family members face with severe problems . lack of father brings financial and management problems and lack of mother psychological problems and lack of integretly in the family . Lack of eachparent removes family balance and changes the most important family function which is proper up bringing children .Research by John Balby has shown that Wrong behavior in one generation due to death or diseuse of parents affect even the future children generation . they cant have normal behaviour and lovely canons . The kind and quality of family members relationship and also quantity of family relationship with persons and networks beyond family, makes social relationship network which is considered social capital of family in sociological literature.